Influence of country risk on the yield of Peru’s sovereign bonds - Castañeda Vargas, Winston Adrián (2021)
The research carried out aims to analyze the degree of influence between country risk measured through EMBIG and the yield of sovereign bonds issued by the public sector of Peru. The study is longitudinal, for which information is taken from the Central Reserve Bank of Peru and a multiple regression model was used to verify the results, in order to establish the degree of causality between both variables. It was concluded that both the dependent variable treated as endogenous and lagged one period, as well as the country risk, significantly influence the yield of sovereign bonds issued by Peru.